Autoantibodies to polymorphonuclear neutrophil elastase do not inhibit but enhance elastase activity - Morcos, Michael; Zimmermann, F.; Radsak, Markus Philipp; Wörner, Inga; Kramer, Michael D.; Roland, J.; Hänsch, Gertrud Maria; Andrassy, Konrad (American journal of kidney diseases, 1998)
Polymorphonuclear neutrophils (PMNs) of patients with active Wegener's granulomatosis and PMN activated in vitro express elastase on their surface as detected by autoantibodies derived from patients with ANCA- positive vasculitis or chronic staphylococcus infections. The PMN- associated elastase was enzymatically active. By affinity-purified autoantibodies to elastase, the enzymatic activity was further enhanced as measured either by a chromogenic peptide or by elastin as substrate. Antibodies to human elastase from mouse or from sheep also enhanced elastase activity, whereas unrelated immunoglobulins had no effect. Taken together, our data indicate that autoantibodies to elastase are not inhibitory but upregulate the elastase activity and thereby might contribute to tissue damage. (Am J Kidney Dis 1998 Jun;31(6):978-85)